Payment Methods in International Trade from Georgian Law Perspective - Gotua, Levan (European Scientific Journal, ESJ, 2026)
This article examines the legal structure and function of payment methods in international trade, focusing on their role as mechanisms of risk allocation and aiming to provide an overview of this topic from Georgian law perspective. It argues that instruments such as letters of credit, documentary collections and open account transactions operate not only as mere commercial tools but also as legal architectures. While Georgian law formally, and in author’s view, to some extent insufficiently, incorporates international trade finance standards through the Civil Code and recognition of international commercial practices, this area still remains underdeveloped in doctrinal articulation and judicial interpretation. Along with using of other scientific methods, this article, above all, by means of comparative analysis with the European Union law, doctrines and practices of EU countries and the framework of the EU–Georgia Deep and Comprehensive Free Trade Area (DCFTA), aims to demonstrate that Georgia’s trade finance system exhibits certain structural dependence on external norms. Accordingly, it concludes with proposing some doctrinal and institutional reforms with the goal of strengthening legal certainty and enhancing judicial engagement with trade finance principles.